Isomerization of long-chain fatty acids and long-chain hydrocarbons: A review. (October 2021) - Maghrebi, R.; Buffi, M.; Bondioli, P.; Chiaramonti, D.
Abstract: Isomerization of long-chain saturated fatty acids (LCSFAs) by catalytic conversion through zeolites is of great interest in cosmetics and biofuel production. This conversion pathway has received attention in the last two decades due to the increasing interest in renewable feedstock. A favorable policy framework and a larger availability of lipid wastes from industry promote new valorization practices like this one and open new opportunities for the near future. Moreover, the next decade is likely to witness a considerable rise in the research for improvement of isomerization yield by testing various bifunctional zeolites. Although this approach has enormous potential in terms of applicability, it currently suffers from low yields that stems from focus on only one type of zeolite. Despite limited number of studies in this field, there is a considerable amount of literature about isomerization of similar compounds, i.e., long-chain unsaturated fatty acids (LCUFAs) and long-chain linear alkanes (LCAs); where, past research has focused on increasing the isomerization yield by using different catalysts, co-catalysts and optimizing operating conditions. Among all types of isomerization catalysts, bifunctional metal loaded microporous solid acids catalysts, known as zeolites, have attracted extensive attention due to their sustainable, environmentally friendly nature, as well as recoverable features. The current challenges of isomerization of LCSFAs are about enhancing the yields towards isomerized products and lowering the long reaction times to scale-up towards industrialization. The innovative aspect of this work is about the identification of the most promising catalysts and co-catalysts for isomerization of LCSFAs and the comparison of isomerization of two similar compounds, LCUFAs and LCAs. It also provides a comprehensive overview of the current state of the art. Results show that the best yields for isomerization of LCUFAs and LCAs have been obtained by 1-dimensional and 2-dimensional zeolites; while, 3-dimensional zeolites have shown the lowest isomerization yields. It also indicates that, for isomerization of LCSFAs, 3-dimensioanl zeolites are the only category that have been tested. Thus, the present paper, highlights shortcomings and provides a blueprint for future research on isomerization of LCSFAs. Highlights: A literature review on isomerization of LCUFAs and LCAs was carried out to address LCSFA. The most promising catalysts and co-catalysts for isomerization of LCSFAs were identified. Best isomerization yields of LCUFAs and LCAs obtained by 1-D and 2-D zeolites. Isomerization yields for LCSFAs can be improved significantly using continuous systems. Isomerization of LCSFAs, LCUFAs, and LCAs can be done by similar catalysts.